Perbaikan Faktor Daya Beban Industri Rumah Tangga dengan Menggunakan Capasitor Bank - R, Syafruddin (Media Nusantara, 2021)
Monthly electricity costs CV. Karna Jaya Industrial Engineering is quite large, from the results of measurements made at the CV. Karna Jaya Industrial Engineering has a very low power factor of 0.56. The installation of capacitors is the right choice in terms of if you want to increase the power factor of an electrical network. To improve the power factor to 0.9then CV. Karna Jaya Teknik must install a capacitor of 32.4141 farads when connected to a star and a capacitor of 10.8047 farads when connected to a delta, the ratio C? /CY = 10.8047/32.4141 = 1/3 or CY = 3 C? . By installing a capacitor bank , it can reduce the reactive power which previously ranged from 4003.39 VAR to 2435.4 VAR, meaning that there is a savings in electricity costs of 1567.99 VAR. We recommend that the installation of a capacitor bank use a delta connection because the price is 1/3 of the star connection. An investment of IDR 1567990 for the installation of a bank capacitor is 1567.99 VAR using a bank loan with a bank rate = 15%/year. Then Breaks Event Point in 2 months.